Environmental Effects of Brick Making on a Wetland Ecosystem: A Case Study of Kakiizi Wetland Ntungamo District. - Nimusiima, Nicholas (Kabale University, 2024)
A wetland is a distinct semi-aquatic ecosystem whose groundcovers are flooded or saturated in water, either permanently, for years or decades, or only seasonally for shorter periods. Wetlands play crucial roles ranging from water purification, provision of a wide range of wildlife habitat and flood control among others. Due to constant brick making, Kakiizi wetland has gone through a continuous destruction due to unlimited brick-making activities hence reducing this wetland roles. The study was to assess the impact of brick-making on the Ecosystem of kakiizi wetland in Itojo sub-county, Ntungamo district, in South Western Uganda, following the study objectives, which were: to assess the effects of brick-making on plant species richness and diversity of kakiizi wetland Ntungamo district and to analyze the effects of brick-making on physical properties of water of kakiizi wetland Ntungamo District. The results indicated a reduced abundance of plant species in disturbed areas than in intact sampling areas. Reduced species richness was due to increased ranges of water physical parameters as a result of brick-making activity which led to destruction and undergrowth of different wetland plant species. Findings of the study revealed that the affected parts of the wetland had limited plant richness and increased ranges of water physical parameters most especially PH, Electrical conductivity, and temperature. From the findings, it was evidenced that sedges are more likely to survive the effect of brick-making compared to other species. I therefore recommend that if a wetland is left for sometimes following its destruction, the wetland will regenerate and provide the same ecological functions for instance sedges were observed to generate very quickly if given enough time.